2015
DOI: 10.4077/cjp.2015.bad273
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of an Aqueous Extract of Futokadsura Stem in an Aβ-Induced Alzheimer's Disease-Like Rat Model

Abstract: Futokadsura stem has been traditionally used to dispel wind-damp obstruction syndrome manifested as painful and stiff joints, tendon and muscle spasms, lower back pain, painful knees and pain from external injury. An aqueous extract of Futokadsura stem has previously been found to have neuro-protective effects in vitro. In this study, we aimed to investigate if the Futokadsura stem extract could protect the neuron in the brain of an Aβ-induced Alzheimer's Disease (AD)-like rat model by improving the learning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…TNF-α is a critical factor in the pathogenesis of multiple inflammatory symptoms [131], and down-regulation of TNF-α reduces expressions of inflammatory factors in chronic inflammatory diseases [132,133]. Other studies in the rodent have similarly demonstrated that castration increases TNF-α secretion in the macrophage [134], and IL-6 in the serum and bone marrow [133,134,135,136]. The spleen is a unique and important innate as well as an adaptive immunity organ [137].…”
Section: Sex Steroid Hormones Modulate the Pathophysiology Of Inflmentioning
confidence: 99%
“…TNF-α is a critical factor in the pathogenesis of multiple inflammatory symptoms [131], and down-regulation of TNF-α reduces expressions of inflammatory factors in chronic inflammatory diseases [132,133]. Other studies in the rodent have similarly demonstrated that castration increases TNF-α secretion in the macrophage [134], and IL-6 in the serum and bone marrow [133,134,135,136]. The spleen is a unique and important innate as well as an adaptive immunity organ [137].…”
Section: Sex Steroid Hormones Modulate the Pathophysiology Of Inflmentioning
confidence: 99%
“…Previous studies have reported that increased Th17 cells as a new unique subpopulation of CD4 + T cells may play a role in the pathogenesis of BA. Th17 cells exert their function by secreting IL-17α, which has a variety of effects, including induction of proinflammatory cytokines such as IL-23, IL-6, IL-8 and IL-1 as well as chemokines such as CXCL1, CXCL2, CXCL3, CXCL6 (GCP-2), CXCL8 (IL-8), CCL2 (MCP-1) and CCL (CC-chemokine ligand)-20, which mediate infiltration of tissue inflammatory cells (22,36,37). This suggests that promoting the production of these cytokines and chemokines is an important inflammatory processes in biliary injury of BA.…”
Section: Discussionmentioning
confidence: 99%